Prevalence of Noise-Induced Hearing Loss among Textile Industry Workers in Dar es Salaam, Tanzania - Zephania Abraham; Enica Massawe; Daudi Ntunaguzi; Aveline Kahinga; Shaban Mawala (Ubiquity Press, 2019)
Background: Noise-induced hearing loss (NIHL) is the most common preventable cause of deafness. The degree of NIHL is determined by intensity, duration of exposure, spectral characteristics of the noise, and individual susceptibility. Industrial workers in both developed and developing countries are all at risk of suffering from NIHL. Methods: An industry-based descriptive cross-sectional study was conducted. Data was collected using structured questionnaires, where sound intensity and hearing assessment were measured using a portable sound level meter and a portable audiometer, respectively. Data was analyzed using Statistical Package for Social Sciences (SPSS) program version 21. Findings: Out of 265 industrial workers who were recruited in this study, 161 (60.8%) were males and the predominant age group was 22 to 35 years (43%). The prevalence of NIHL was found to be 58.5%. Of 155 workers with NIHL, 101 (67.7%) were males. The most common age group was greater than 49 years. Of those with work experience from 5 to 10 years, only 38.5% had NIHL. The most common symptom was hearing loss, accounting for 24.9% of cases. Conclusion: The overall prevalence of NIHL was higher in textile industry workers. The prevalence was higher in males, older workers, and those who experienced prolonged exposure.